Prevalence of Hip Dysplasia and Associated Conditions in Children Treated for Idiopathic Early-onset Scoliosis—Don't Just Look at the Spine. Issue 1 (January 2020) - Talmage, Matthew S.; Nielson, Alexandra N.; Heflin, John A.; D'Astous, Jacques L.; Fedorak, Graham T.
Abstract : Background: Hip dysplasia, congenital muscular torticollis, plagiocephaly, and metatarsus adductus are known to be associated. The etiology of infantile idiopathic scoliosis and its association with the aforementioned conditions is unknown. This study reviews a series of infantile scoliosis patients to address this gap. Methods: The medical records of all patients treated with casting for early-onset scoliosis (EOS) from 2001 to 2016 were retrospectively reviewed. Inclusion criteria were a diagnosis of idiopathic EOS and age below 4 years at the time of the first cast. Demographic information, comorbid conditions, and radiographic measurements including Cobb angle and acetabular index (AI) were collected. The first acceptable anteroposterior pelvis radiograph for each patient was measured. An AI≥30 degrees was defined as hip dysplasia. A measurement between 25 and 30 degrees was defined as a "hip at risk." Results: Between 2001 and 2016, 142 patients were treated with casting. Eighty-one patients met the inclusion criteria. The mean age at the first cast was 19.3 (±7.5) months and the mean Cobb angle was 53.6 (±18.8) degrees. There was no significant correlation between Cobb angle and AI. Nine patients met radiographic criteria for hip dysplasia (11.1%), only 4 of whom had been previously diagnosed. Thirty-six patients (44.4%) met the criteria of having at least 1 hip "at risk" of hip dysplasia. Ten patients (12.3%) had been diagnosed with torticollis and 13 patients (16.0%) with plagiocephaly. Three patients (3.7%) had been diagnosed with metatarsus adductus or clubfoot. In total, 30.9% of patients (25/81) had at least one of the above comorbid conditions. Conclusions: In a large group of children treated for idiopathic EOS, we found a high prevalence of commonly associated conditions—hip dysplasia, torticollis, plagiocephaly, metatarsus adductus, and clubfoot. In 6.2% of our sample, a diagnosis of hip dysplasia was not made in a timely manner despite routine radiographic spine follow-up. With increasing subspecialization within pediatric orthopaedics, surgeons need to maintain vigilance in assessing the entire child. Level of Evidence: Level IV.